Grid Requirements for the Integration of Biomedical Information Resources for Health Applications - Oliveira, I. C.; Oliveira, J. L.; Sanchez, J. P.; López-Alonso, V.; Martin-Sanchez, F.; Maojo, V.; Sousa Pereira, A. (Methods of Information in Medicine, 2005)
Objectives: The goal of this paper is to identify how Grid technology can be applied for the development and deployment of integration systems, bringing together distributed and heterogeneous biomedical information sources for medical applications.Methods: The integration of new genetic and medical knowledge in clinical workflows requires the development of new paradigms for information management in which the ability to access and relate disparate data sources is essential. We adopt a requirements perspective based on the user needs we have identified in the development of the INFOGENMED system to assess current Grid technology against those requirements.Results: The gap between Grid features and distributed biomedical information integration needs is characterized. Results from prospective studies are also reported.Conclusions: Grid infrastructures offer advanced features for the deployment of collaborative computational environments across virtual organizations. New Grid developments are in line with the problem of multiple site information integration. From the INFOGENMED point of view, Grid infrastructures need to evolve to implement structured data access services and semantic content description and discovery.
Keywords: Grid technology; medical informatics; computational biology; systems integration; health applications